A critical examination of Evangelicalism in South Africa, with special reference to the Evangelical Witness document and concerned evangelicals - Lund, Christopher Alan (University of Cape Town, 2015)
Bibliography: pages 118-126. === This dissertation arises out of a recognition of the need for research into evangelicalism as a distinct and important area within the Christian church in South Africa. It focuses on the struggle for the symbols and doctrines of the evangelical tradition in South Africa as that struggle is articulated in the Evangelical Witness document (EWISA), and the Concerned Evangelicals organisation (CE), with which the document is associated. Evangelicalism is approached as the site of a struggle for certain theological elements, which have a particular material force as ideology. This struggle is discussed in four chapters. The first chapter discusses the way in which evangelicalism may be defined, suggesting that the struggle over the definition of evangelicalism is itself an indication of wider struggles in evangelicalism. It then develops a brief working model of evangelicalism in South Africa as a framework for understanding CE and EWISA and their critique. The second chapter addresses the EWISA document in some detail, focussing on the way in which EWISA's restatement of certain tenets of evangelical theology has a particular material (ideological) force. The third chapter provides a brief history of CE, and discusses its main agenda as it has been articulated thus far. The final chapter reflects on CE and EWISA's major contributions, indicates some parallel movements in the One Third World and other parts of the Two Thirds World, and makes certain theological and practical recommendations for CE's ongoing work. The main thesis argued is that the liberation critique offered by CE and EWISA shows the need for a reassessment and restatement of evangelicalism in South Africa. Some of the ways in which this restatement may occur are tentatively suggested through an analysis of CE and EWISA's retrieval of certain elements of the evangelical tradition for its project of liberation. This, it is suggested, forms an important beginning for the reclaiming of evangelicalism from the right wing of the evangelical community.